Handbook of Synthetic Photochemistry 2009
DOI: 10.1002/9783527628193.ch2
|View full text |Cite
|
Sign up to set email alerts
|

CarbonCarbon Bond Formation by the Photoelimination of Small Molecules in Solution and in Crystals

Abstract: The formation of CÀC bonds is arguably the most important reaction in organic synthesis. While many strategies have been developed to link organic fragments with a wide range of thermal processes, photochemical syntheses based on the elimination of a small molecule, X (Scheme 2.1), offer significant advantages when the desired structures are highly strained or hindered. In this chapter, we will describe examples of the generation of CÀC bonds through the photoinduced extrusion of small molecules such as N 2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 103 publications
1
14
0
Order By: Relevance
“…Considering that the radical stabilizing energy that results from two α-phenyl groups (RSE ≥ 20.5 kcal/mol) is significantly larger than the values known to enable the reaction (RSE ≥ 11 kcal/mol), one may expect the α-cleavage reaction in ketones 1a – 1c to be very fast and quantum efficiency for the solid state reactions to be high, especially if the reaction were to proceed exclusively from the triplet excited state. However, an increase in the radical stabilization of the α-substituents also increases the rate of α-cleavage from the singlet excited state, so that formation of 1 RP-1 (step 3′ in Scheme ) may compete with intersystem crossing (step 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the radical stabilizing energy that results from two α-phenyl groups (RSE ≥ 20.5 kcal/mol) is significantly larger than the values known to enable the reaction (RSE ≥ 11 kcal/mol), one may expect the α-cleavage reaction in ketones 1a – 1c to be very fast and quantum efficiency for the solid state reactions to be high, especially if the reaction were to proceed exclusively from the triplet excited state. However, an increase in the radical stabilization of the α-substituents also increases the rate of α-cleavage from the singlet excited state, so that formation of 1 RP-1 (step 3′ in Scheme ) may compete with intersystem crossing (step 2).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, nanocrystals with sizes smaller than the wavelength of light can be seen as a state in transition between supramolecular entities and bulk crystals, with strongly reduced scattering, dichroism, and birefringence that enable their measurement by transmission spectroscopy methods, including laser flash photolysis . With that in mind, it is now possible to address subtle mechanistic aspects of several solid-state photoreactions, including the photoinduced decarbonylation of crystalline ketones with radical stabilizing substituents at the two α-positions, such as aryl-susbtituted ketones 1a – 1c in Scheme and Scheme . , The reaction is expected to proceed by an initial α-cleavage of the weakest C–C bond and ultimately results in the formation of product 2 , which maintains the stereochemical information on the reactant by the stereospecific formation of a sterically congested C–C bond. , As indicated in Scheme , the reaction starts by electronic excitation (step 1, Scheme ), which results in the sequential cleavage of the two α-bonds (steps 3 and 6) to generate, respectively, radical pairs RP-1 and RP-2 , which can exist either in a singlet or a triple state . It has been reported that reactions in crystals require the two bond-cleavage steps to be exothermic, and with α-substituents that provide radical stabilization energies (RSEs) greater than 11 kcal/mol, this requirement is easily met in ketones with aryl groups on both α-carbons (the RSE of an α-phenyl group is 16.5 kcal/mol) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, sulfonamide antibiotics, a class of pollutants ubiquitous in the environment, are known to undergo SO 2 extrusion via direct and indirect photolysis, sulfate radical-mediated oxidation, and other oxidation processes. In particular, SO 2 extrusion was proposed to be the primary photodegradation route for five six-membered sulfonamides, and sulfate was reported among the photoproducts . Photoinduced extrusion of SO 2 from organic sulfones is also exploited in synthetic organic chemistry as a mild route to form new C–C bonds, both via direct (requiring a chromophore β to the sulfone) and triplet-induced photolysis. , Unfortunately, the organic chemistry literature is limited to reactions performed in organic solvents and with the specific aim of obtaining highly unstable ring structures for further synthetic transformations . Further research is needed to assess whether natural sulfones and other DOS components can liberate SO 2 upon photolysis under environmentally relevant conditions.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…We have shown that energetic profiles, such as the one represented in Scheme , are helpful for reactions to occur in the crystalline state . In the absence of collisions, rotations, and conformational motions, reactions in crystals must be nearly barrierless.…”
Section: Engineering Reactions In Crystals Part I: Molecular Informat...mentioning
confidence: 99%